(untitled) (Research, Society and Development, 2022)
This article analyzes the differentials of the DSOP methodology (Diagnose, Dream, Budget, and Save), as a financial education tool for basic education students. How short, medium, and long-term dreams are prioritized within the personal budget in the DSOP method is unique, which makes it different from the main methodologies and concepts of personal or family Financial Education. This article aimed to present the differences in the implementation of financial education in basic education according to the DSOP methodology through an integrative literature review. Additionally, a comparative analysis was also carried out with the approach of the theme, Financial Education, used in three textbooks of the 9th year of elementary school. The results highlight the insertion of Financial Education in the school context of basic education in a critical perspective, addressing discussions that are not limited to “save today to buy tomorrow” but that aim to mobilize reflection environments so that students can make critical decisions and use strategies to ensure continuity in the execution of financial planning.